Metal free oxidation of vinamidine derivatives: a simple synthesis of α-keto-β-diimine ligands. Issue 67 (14th November 2018) - Tripathi, Monika; Regnier, Vianney; Ziani, Zakaria; Devillard, Marc; Philouze, Christian; Martin, David
Abstract : Oxidation of vinamidinium salts with meta -chloroperbenzoic acid not only provides access to new persistent 1, 3-di(amino)oxyallyl radical cations, but also to α-keto-β-diimine ligands, for which no convenient synthesis was previously available. Abstract : Oxidation of vinamidinium salts with meta -chloroperbenzoic acid is the key synthetic step towards new persistent 1, 3-di(amino)oxyallyl radical cations. When applied to parent vinamidines, this protocol allows for a simple straightforward synthesis of α-keto-β-diimine ligands, for which no convenient synthesis was previously available.